PENGARUH KOORDINASI DAN KOMUNIKASI TERHADAP EFEKTIVITAS ORGANISASI DI PROVINSI JAMBI - Enadarlita, Enadarlita; Asvio, Nova (Graduate Program Magister Manajemen Pendidikan, 2019)
This study aims to analyze the magnitude of influence 1) Coordination of increasing organizational effectiveness of Jambi Province. 2) Communication to increase the effectiveness of organizations in Jambi Province. 3) Coordination and communication to increase the effectiveness of organizations in Jambi Province. 4) Communication on improving coordination of Jambi Province. This research uses quantitative methods with the type of survey approach. Data collection techniques are carried out by interviews, observations, questionnaires, and documentation. Based on the results of data analysis, the conclusions that can be drawn from this study are 1) there is an influence between coordination on organizational effectiveness because the significance value of 0.010 <0.05, has a beta coefficient of 1.689. coefficient is positive which means that the better the coordination, the better the effectiveness of the organization, Ho is rejected. 2) There is no influence between communication on organizational effectiveness because the significance value of 0.203> 0.05, has a beta coefficient of -1.267. coefficients are negative, which means that even though good communication does not guarantee increasing organizational effectiveness, vice versa, Ho is accepted. 3) There is an influence between coordination and communication on organizational effectiveness because the sign level is 0.0001 <0.05, meaning that if coordination and communication are carried out together well, then the effectiveness of the organization will also increase and vice versa, Ho is rejected.